Improve Cardiac Emergency Preparedness by Building a Team-Based Cardiopulmonary Resuscitation Educational Plan - Xu, Jianing; Dong, Xuejie; Yin, Hongfan; Guan, Zhouyu; Li, Zhenghao; Qu, Fangge; Chen, Tian; Wang, Caifeng; Fang, Qiong; Zhang, Lin (Frontiers in Public Health, 2022)
Objective: To design an innovative team-based cardiopulmonary resuscitation (CPR) educational plan for multiple bystanders and evaluate whether it was associated with better teamwork and higher quality of resuscitation. Methods: The team-based CPR plan defined the process for a three-person team emphasizing task allocation, leadership, and closed-loop communication. Participants qualified for single-rescuer CPR skills were randomized into teams of 3. The teamwork performance and CPR operation skills were evaluated in one simulated cardiac arrest scenario before and after training on the team-based CPR plan. The primary outcomes were measured by Team Emergency Assessment Measure (TEAM) scale and chest compression fraction (CCF). Results: Forty-three teams were included in the analysis. The team-based CPR plan significantly improved the team performance (Global rating 6.7±1.3 vs 9.0±0.7, corrected P<0.001 after Bonferroni’s correction). CCF was improved [median 59 (IQR 48–69) vs 64 (IQR 57–71) %, corrected P=0.002] as hands-off time was significantly decreased [median 233.2 (IQR 181.0–264.0) vs 207 (IQR 174–222.9) s, corrected P=0.02] after applied the team-based CPR plan. We found the average compression depth was significantly improved through the team-based CPR training [median 5.1 (IQR 4.7–5.6) vs 5.3 (IQR 4.9–5.5) cm, P=0.03] but no more significantly after applying the Bonferroni’s correction (corrected P=0.35). The compression depths were significantly improved by collaborating and exchanging the role of compression among the participants after the 6th minute. Conclusion: The team-based CPR plan is feasible to enhance the teamwork performance by bystanders and effectiveness to improve the resuscitation quality in prearrival care. We suggest a wide application of the team-based CPR plan in the educational program for better resuscitation performance in real rescue events.